2019
DOI: 10.1177/0143624419840768
|View full text |Cite
|
Sign up to set email alerts
|

A London residential retrofit case study: Evaluating passive mitigation methods of reducing risk to overheating through the use of solar shading combined with night-time ventilation

Abstract: Overheating in the indoor environment, specifically in domestic homes, schools and healthcare settings has become of great concern to us in the UK. This is due to frequent hot weather events as a result of the continually rising global average temperatures. Overheating is a result of the heat gains associated with occupancy and solar heat gains trapped in the internal environment. The continuing rise in global average temperatures and improved insulation standards necessary to mitigate heat losses during the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…They found that passive adaptations were not capable of eliminating overheating entirely, and by the 2080s active cooling was likely to be required to maintain comfortable indoor conditions in lofts. Grussa et al [3] evaluated passive mitigation methods of reducing overheating risk through the use of solar shading combined with night-time ventilation based on a case study. They recommended that the interrelationship between glazing, shading, and ventilation (amongst other variables) need to be collectively evaluated at the planning stage to ensure the appropriate design of an effective management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…They found that passive adaptations were not capable of eliminating overheating entirely, and by the 2080s active cooling was likely to be required to maintain comfortable indoor conditions in lofts. Grussa et al [3] evaluated passive mitigation methods of reducing overheating risk through the use of solar shading combined with night-time ventilation based on a case study. They recommended that the interrelationship between glazing, shading, and ventilation (amongst other variables) need to be collectively evaluated at the planning stage to ensure the appropriate design of an effective management strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, walls with internally applied insulation, combined with low ventilation, could also result in a higher chance of overheating in the future [65]. Likewise, while shading reduces overheating in the summer, it increases the winter heating demand [90,95]. These examples illustrate the importance of having a good set of climate-adaptive measures to achieve the benefits desired by homeowners over a range of climate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have identified solar shading as an effective passive cooling strategy for reducing overheating, 13,15,16,33,75,[94][95][96][97] its application in the UK may be limited due to the prevalence of outward window openings that external shadings could block. 98 In addition, solar shading reduces daylighting, which may affect occupants' productivity and wellbeing. Habitzreuter, Smith and Keeling 70 found that external shading reduced overheating and daylighting by 74% and 30%, respectively.…”
Section: Heat and Solar Protectionmentioning
confidence: 99%